Towards a Product Line for Electronic Shelf Labels Domain - Teixeira, Leonardo Venâncio; Oliveira, André Luiz de; Valente, Fredy João; Ferrari, Fabiano; Camargo, Valter Vieira de (Anais do Workshop de Visualização, Evolução e Manutenção de Software (VEM); 2024: Anais do XII Workshop de Visualização, Evolução e Manutenção de SoftwareDO - 10.5753/vem.2024.3902, 2024)
Electronic Shelf Labels are devices used to dynamically display sales price tags and other product information on the retail shop floor. It is an Internet of Things (IoT) technology that defines a new system domain; the Electronic Shelf Labels (ESL) Domain. Developing solutions for this domain is challenging due to the distributed nature of these applications, and the high degree of variabilities and features. Software Product Lines is an approach that is able to model a domain so that one can facilitate the generation of specific products from this domain. Although the development of this kind of application is complex, currently there are no proposed approaches for making the development easier by means of tools/methodologies. The goal of this paper is to present our initial steps towards the definition of a product line for ESL solutions. The approach we are following for domain analysis is based on two main sources: i) white and grey literature and ii) an existing ESL solution. These two sources provide us with theoretical and technical information from the domain. Our preliminary results include a feature diagram and a mapping table that can be used for generating products from the SPL.